GENDER DIFFERENTIALS AND PROFITABILITY ANALYSIS OF PEPPER (CAPSICUM SPECIES) PRODUCTION, KADUNA STATE, NIGERIA (American International Journal of Agricultural Studies, 2023)
This study analyzed gender differentials and profitability of pepper (Capsicum species) production in Kaduna State, Nigeria. Multi-stage sampling technique was adopted. One hundred pepper farmers were selected. Primary sources of data were employed with the aid of well-designed and well-structured questionnaire. The results show that 66% of pepper farmers were between 21 to 50 years. Pepper production was profitable in the study area. Gender differentials in average costs and returns in pepper production revealed that gross margin were 137, 556.51 Naira per hectare for male pepper farmers, higher than that at 109,711.77 Naira per hectare for female pepper farmers respectively. Gender differentials in factors influencing output of pepper produced shows that age ,and fertilizer input , were significant factors influencing output of pepper produced by male farmers at 1% probability levels, while age , labour input , and fertilizer input , were significant factors influencing output of pepper produced by female farmers at 1% probability levels respectively. The return to scale of pepper production was estimated at 2.798 for male farmers, which signifies increasing return to scale.  The return to scale  was calculated for female pepper farmers at 0.033, which implies decrease return to scale. Major constraints faced by pepper farmers were: lack of fertilizers, pest and disease infestations, and inadequate capital. The study recommends that women pepper farmers should be giving more access to farm inputs and credit facilities at low interest rate to increase productivity.  JEL Classification Codes: Q1, Q2, Q5.